2020
DOI: 10.3390/w12040991
|View full text |Cite
|
Sign up to set email alerts
|

Differences of Regulative Flexibility between Hydrological Isolated and Connected Lakes in a Large Floodplain: Insight from Inundation Dynamics and Landscape Heterogeneity

Abstract: The inundation areas of floodplains are crucial to wetland ecosystems, especially in supporting biodiversity. Accurately identifying the spatial and temporal patterns of inundation areas is important for understanding floodplain ecosystem processes. Here, lakes in the Yangtze River Floodplain were divided into two types according to hydrological conditions: the natural connected lakes (Dongting Lake and Poyang Lake) with natural water level fluctuations and the isolated lakes (lakes in Jianghan Plain) with sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…According to the results of this study, WBI and NDWI indices helped to recognise saturated soil and also NDII and LSWI indices showed better dynamic range of recognition due to stronger absorption of infrared rays to display different degrees of soil moisture. Other studies by these authors have shown that hydrological regimes such as flood frequency and inundation area determine habitat quality affect vegetation cover and biomass [8].…”
Section: Literature Reviewmentioning
confidence: 89%
“…According to the results of this study, WBI and NDWI indices helped to recognise saturated soil and also NDII and LSWI indices showed better dynamic range of recognition due to stronger absorption of infrared rays to display different degrees of soil moisture. Other studies by these authors have shown that hydrological regimes such as flood frequency and inundation area determine habitat quality affect vegetation cover and biomass [8].…”
Section: Literature Reviewmentioning
confidence: 89%
“…Based on the filtered Landsat data (Table S2 in Supporting Information ), the water extraction method in J. K. Teng et al. (2020) was used to obtain the water surface distribution and area (X. Wang et al., 2018). The formula is in Supporting Information (Text S1 in Supporting Information ). Water body patch density (PD).…”
Section: Methodsmentioning
confidence: 99%
“…The formula is in Supporting Information (Text S1 in Supporting Information ). Water body patch density (PD). Patch density is used to measure the degree of landscape fragmentation (J. K. Teng et al., 2020) which reflects the spatial configuration and structural composition at the landscape scale (Hein et al., 2004). We calculate the water body patch density to analyze the change characteristics of Poyang Lake hydrology in distribution and structure.…”
Section: Methodsmentioning
confidence: 99%
“…The lake-inundated area refers to the area that was judged to have appeared as water during the study period, except for the area of the perennial stable lakes [45]. The inundation frequency refers to the proportion of the inundated time of a certain area to the total inundated time during the study period.…”
Section: Lake Inundation Area Divisionmentioning
confidence: 99%